2010
DOI: 10.5423/ppj.2010.26.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Potato White Mold Using Coniothyrium minitans and Resistance of Potato Cultivars to Sclerotinia sclerotiorum

Abstract: This study was conducted in Bahar and Lalehjin, Hamadan, Iran to assess the biocontrol efficacy of Coniothyrium minitans Campbell against potato white mold caused by Sclerotinia sclerotiorum (Lib.) de Bary under field and greenhouse conditions. In addition, the resistance of common potato cultivars against S. sclerotiorum was determined in a greenhouse experiment. After straw inoculation of six potato cultivars (Pashandi, Istambouli, Agria, Marfauna, Alpha and Spartaan) with S. sclerotiorum, the least disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The previous studies have shown that the applications of biocontrol agents such as Trichoderma spp., Talaromyces flavus (Ojaghian, 2011) and Coniothyrium minitans (Ojaghian, 2010) have potential to markedly reduce the disease incidence of potato stem rot. In addition, biofumigation caused by Brassica crops was able to decrease incidence of the disease in potato fields of Hamedan (Ojaghian et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have shown that the applications of biocontrol agents such as Trichoderma spp., Talaromyces flavus (Ojaghian, 2011) and Coniothyrium minitans (Ojaghian, 2010) have potential to markedly reduce the disease incidence of potato stem rot. In addition, biofumigation caused by Brassica crops was able to decrease incidence of the disease in potato fields of Hamedan (Ojaghian et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although some biocontrol agents have been effective against the disease (Ojaghian, 2010(Ojaghian, , 2011, the major control method used by potato growers against white mold is application of fungicides mainly iprodione and dichloran (Ojaghian et al, 2015) which has caused a progressive pollution of underwaters (Data not published). Furthermore, fungicide resistance against Sclerotinia spp.…”
Section: Introductionmentioning
confidence: 99%
“…The S. sclerotiorum is a ubiquitous phytopathogen which infects many dicotyledonous plants including Brassica crops. Although many research have been conducted to assess control measures against Sclerotinia diseases on different crops, [4][5][6][7][8][9][10] no research has been found about nonchemical methods against tuber mustard white rot. The in vitro antifungal effect of tested chitosans and ASA was evaluated in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to assess the antifungal efficacy of cinnamon bark and rosemary leaves against three isolates of S. sclerotiorum . In previous researches, we assessed the biocontrol efficacy of Trichoderma spp., Coniothyrium minitans Campbell and Brassica biofumigation against this pathogen (Ojaghian, , ; Ojaghian et al , 2012 a , b ). Although Soylu et al () showed the potential of essential oils from oregano ( Origanum syriacum L.) and fennel ( Foeniculum vulgare Mill.)…”
Section: Discussionmentioning
confidence: 99%